2019
DOI: 10.1002/ange.201908968
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Incorporation of Nitrides into W‐Fe‐S Clusters

Abstract: Incorporation of monatomic 2p ligands into the core of iron–sulfur clusters has been researched since the discovery of interstitial carbide in the FeMo cofactor of Mo‐dependent nitrogenase, but has proven to be a synthetic challenge. Herein, two distinct synthetic pathways are rationalized to install nitride ligands into targeted positions of W‐Fe‐S clusters, generating unprecedented nitride‐ligated iron–sulfur clusters, namely [(Tp*)2W2Fe6(μ4‐N)2S6L4]2− (Tp*=tris(3,5‐dimethyl‐1‐pyrazolyl)hydroborate(1−), L=Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In 2002, the identification of an unspecified interstitial light atom missing from the 1992 crystal structure of FeMoco led to attempts to synthesize iron–sulfur clusters with various light atom incorporations (Figure ). Successes include an oxo-containing [Fe 8 S 6 O] cluster from Tatsumi ( V ), an imido-containing [Fe 4 S 3 N tBu ] cubane from Lee ( VI ), and more recently a heterometal-imido [WFe 3 S 3 NSiMe 3 ] cubane ( VII ) and a heterometal-nitrido [WFe 3 S 3 N] 2 edge-bridge double cubane ( VIII ) from Holm and Chen. The oxo-cluster reported by Tatsumi was prepared through a similar self-assembly reaction to that described in Figure for the analogous all-sulfide complex with the addition of water and use of a mixed thiolate-alkoxide Fe dimer precursor.…”
Section: Characterizing N2ases Through Model Chemistrymentioning
confidence: 99%
“…In 2002, the identification of an unspecified interstitial light atom missing from the 1992 crystal structure of FeMoco led to attempts to synthesize iron–sulfur clusters with various light atom incorporations (Figure ). Successes include an oxo-containing [Fe 8 S 6 O] cluster from Tatsumi ( V ), an imido-containing [Fe 4 S 3 N tBu ] cubane from Lee ( VI ), and more recently a heterometal-imido [WFe 3 S 3 NSiMe 3 ] cubane ( VII ) and a heterometal-nitrido [WFe 3 S 3 N] 2 edge-bridge double cubane ( VIII ) from Holm and Chen. The oxo-cluster reported by Tatsumi was prepared through a similar self-assembly reaction to that described in Figure for the analogous all-sulfide complex with the addition of water and use of a mixed thiolate-alkoxide Fe dimer precursor.…”
Section: Characterizing N2ases Through Model Chemistrymentioning
confidence: 99%
“…Periodontal disease is the most common oral disease in the world. As part of the human oral microbiome, the Gramnegative anaerobic bacterium Porphyromonas gingivalis plays a crucial role in the occurrence and development of periodontal disease (Xu et al, 2020). In addition to locating in the oral cavity, P. gingivalis can easily invade the respiratory tract, the digestive tract and the blood, causing systemic disease (Haraszthy et al, 2000;Patrakka et al, 2019;Harding et al, 2017;Dominy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, many periodontitis patients respond poorly to antibiotics (Colombo et al, 2009); thus, an 'antivirulence' therapy approach has been promoted that targets the virulence factors of specific periodontal pathogens, including P. gingivalis. Studies revealed that P. gingivalis has a number of virulence factors (Xu et al, 2020), including the well studied enzymes known as sialidases and also termed neuraminidases (Acun ˜a-Amador et al, 2018). Not limited to P. gingivalis, sialidases are well established virulence factors in many pathogenic microorganisms, including Streptococcus pneumoniae, Propionibacterium acnes, Vibrio cholerae and Tannerella forsythia (Gualdi et al, 2012;Ho ¨fler et al, 1981;Kaisar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bi-and multimetallic synthetic analogs focused on interrogating the role of the interstitial atom and multimetallic effects have been targeted (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), but complexes that display bridging carbide (11,(24)(25)(26)(27) or even carbyne (9,10,28) ligands are rare. Carbide-containing Fe clusters display four to six metal centers but invariably are rich in CO ligands (24,25,27).…”
mentioning
confidence: 99%